Correction: Polymorphism and solid–solid phase transitions of hydrogen bonded 2-adamantanol and 2-methyl-2-adamantanol compounds. Issue 30 (11th July 2022) - Salvatori, Alejandro; Negrier, Philippe; Massip, Stephane; Muñoz-Duque, Antonio; Lloveras, Pol; Barrio, Maria; Tamarit, Josep-Lluís
Abstract : Correction for 'Polymorphism and solid–solid phase transitions of hydrogen bonded 2-adamantanol and 2-methyl-2-adamantanol compounds' by Alejandro Salvatori et al., CrystEngComm, 2022, 24, 3692–3700, ; https://doi.org/10.1039/D2CE00324D .